2023
DOI: 10.3390/cancers15092568
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and Basic Research Strategies for Overcoming Resistance to Targeted Therapies in HER2-Positive Breast Cancer

Abstract: The amplification of epidermal growth factor receptor 2 (HER2) is associated with a poor prognosis and HER2 gene is overexpressed in approximately 15–30% of breast cancers. In HER2-positive breast cancer patients, HER2-targeted therapies improved clinical outcomes and survival rates. However, drug resistance to anti-HER2 drugs is almost unavoidable, leaving some patients with an unmet need for better prognoses. Therefore, exploring strategies to delay or revert drug resistance is urgent. In recent years, new t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 139 publications
(155 reference statements)
0
3
0
Order By: Relevance
“…Overexpression of HER2, found in 15–30% of all breast cancers, is associated with metastasis and poor prognosis. Targeting of HER2 has greatly increased patient survival in breast cancer, but development of drug resistance is still a major therapeutic obstacle [ 313 ]. A recent study by Hansen et al showed that overexpression of HER2 was associated with invasion-promoting peripheral localization of lysosomes [ 314 ].…”
Section: Lysosomal Involvement In Cancermentioning
confidence: 99%
“…Overexpression of HER2, found in 15–30% of all breast cancers, is associated with metastasis and poor prognosis. Targeting of HER2 has greatly increased patient survival in breast cancer, but development of drug resistance is still a major therapeutic obstacle [ 313 ]. A recent study by Hansen et al showed that overexpression of HER2 was associated with invasion-promoting peripheral localization of lysosomes [ 314 ].…”
Section: Lysosomal Involvement In Cancermentioning
confidence: 99%
“…This approach has revolutionized cancer treatment, leading to improved survival rates and reduced toxicity compared to traditional chemotherapy (10,11). Medicines such as imatinib, which cures chronic myeloid leukemia, and trastuzumab, which treats HER2-positive breast cancer, are prime examples of how medicinal chemistry has revolutionized treatments for cancer (12,13). Moreover, medicinal chemistry has been pivotal in developing antiviral drugs, particularly during the ongoing COVID-19 pandemic (14,15).…”
Section: Dear Editormentioning
confidence: 99%
“…Resistance to targeted therapies is a significant challenge in BCa treatment ( 157 ). BsAbs can potentially target multiple signaling pathways simultaneously, addressing resistance mechanisms and improving treatment responses in resistant or refractory BCa cases ( 7 , 158 ). BsAbs have the advantage of explicitly targeting cancer cells and sparing normal cells, potentially reducing off-target toxicities associated with non-specific treatments ( 80 ).…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%